Bilangan Kromatik Lokasi Subdivisi Operasi Barbel Tertentu Graf Origami \mathbit{B}_{\mathbit{O}_3}^\mathbit{s}, \mathbit{B}_{\mathbit{O}_4}^\mathbit{s}, \mathbit{B}_{\mathbit{O}_5}^\mathbit{s}, \mathbit{B}_{\mathbit{O}_\mathbf - Agus Iriawan; Asmiati Asmiati; La Zakaria; Kurnia Muludi; Bernadhita Herindri Samodra Utami (Jurnal Siger Matematika, 2021)
Let G=(V,E) be a connected graph and c be a proper k-coloring of G with color 1,2,...,k. Let {C_1,C_2,...,C_k} be a partition of V(G) which is induced by coloring c. The color code c_Phi(v) of v is the ordered k-tuple (d(v,C_1),d(v,C_2),...,d(v,C_k)) where d(v,C_i)= min{d(v,x)|x \in C_i} for any i. If all distinct vertices of G have distinct color codes, then c is called k-locating coloring of G. The locating-chromatic number, denoted by χ_L(G), is the smallest k such that G has a locating k-coloring. Subdivision certain barbell origami graphs, for s>=1, is a graph with V\left(B_{O_n}^s\right)=\left\{u_i,u_{n+i},v_i,v_{n+i},w_i,w_{n+i}\middle|1\le i\le n\right\} U {x_i|1<=i<=s} and E\left(B_{O_n}^s\right)={{u}_iw_i,u_iv_i,v_iw_i,u_iu_{i+1},w_iu_{i+1}|1\le i\le n} U {{u}_{n+i}w_{n+i},u_{n+i}v_{n+i},v_{n+i}w_{n+i},u_{n+i}u_{n+i+1},w_{n+i}u_{n+i+1}|1\le i\le n-1} U {u_nx_1,x_nu_{n+1}} U{x_ix_{i+1}|1\le i\le s-1}. In this paper, we will determined the locating-chromatic number of subdivision certain barbell origami graphs B_{O_3}^s,B_{O_4}^s , B_{O_5}^s and B_{O_6}^s.